2008
DOI: 10.1071/ea07251
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dicyandiamide application on nitrous oxide emissions from urine patches in northern Victoria, Australia

Abstract: Animal production systems in Australia are a significant contributor to nitrous oxide (N2O) emissions from soil, with the Australian Greenhouse Gas Inventory attributing ~25% of the N2O emissions from agricultural soils to animal production. Recent studies in New Zealand using dicyandiamide (DCD) in association with the application of urine to pastoral soil have reported reductions in N2O emission of up to 78% and reduced nitrate leaching of up to 45%. As such, the application of DCD to grazed pastures offers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 9 publications
0
16
0
1
Order By: Relevance
“…A fully automated system has operated continuously since 2004 measuring N 2 O fluxes from irrigated and non-irrigated pasture in Victoria, Australia (Kelly et al, 2008), and another system was deployed over a complete sugar cane growth cycle in northern Australia (Denmead et al, 2010). Both studies were based on earlier FTIR systems but provided continuous measurements over periods of months to years.…”
Section: Chamber Measurementsmentioning
confidence: 99%
“…A fully automated system has operated continuously since 2004 measuring N 2 O fluxes from irrigated and non-irrigated pasture in Victoria, Australia (Kelly et al, 2008), and another system was deployed over a complete sugar cane growth cycle in northern Australia (Denmead et al, 2010). Both studies were based on earlier FTIR systems but provided continuous measurements over periods of months to years.…”
Section: Chamber Measurementsmentioning
confidence: 99%
“…Fertilisers coated with nitrification inhibitor have been shown to be effective in reducing nitrification, and N 2 O emissions by up to~80%, as reviewed by (de Klein et al 2001). Applied as a spray, nitrification inhibitors can also be effective in reducing N 2 O emissions from animal urine by 27-91%, with pasture yield increases of 0-36%, depending on the magnitude of N loss (Di et al 2007;Kelly et al 2008;Smith et al 2008). However, many of these studies have been conducted under optimal conditions for N 2 O production and over short periods, so the potential on-farm abatement is likely to be more conservative than the published data.…”
Section: Nitrous Oxidementioning
confidence: 99%
“…More-recent research has shown that the nitrification inhibitor dicyandiamide (DCD) can be fed to a ruminant and be transferred to the urine, targeting the inhibitor where and when required, thus requiring a fraction of the product compared with spraying an entire paddock (Ledgard et al 2007); this technology therefore has potential to be cost-effective in more extensive grazing systems where an offset income could exceed the cost of feeding the inhibitor. Nitrification inhibitors are also temperature-sensitive, as evidenced by lower efficacy reported on dairy pastures in northern Victoria; Kelly et al (2008) reported a 47% reduction in N 2 O from urine patches for~50 days in midspring and 27% reduction in N 2 O for~25 days when applied in midsummer. Their use has historically been restricted, mainly due to cost, and this is likely to remain the case unless there is an added incentive for their adoption.…”
Section: Nitrous Oxidementioning
confidence: 99%
See 1 more Smart Citation
“…The nitrification inhibitors DMPP and DCD have been reported to decrease N 2 O emissions in laboratory studies on Australian soils (DMPP) and in field studies in pasture systems (DCD) (Di et al 2007;Kelly et al 2008;Di et al 2010;Gilsanz et al 2016). A recent review found them effective in temperate grassland-based agriculture (Li et al 2013a).…”
Section: Introductionmentioning
confidence: 99%